EXPERIMENTAL STUDY OF INFLUENCE OF FINE DROP MOISTURE AND CONTAMINANTS IN HEAT CARRIER ON COEFFICIENT OF HEAT REMOVAL OF VORTEX HEAT EXCHANGER OF GAS CONTROL STATION HEATING SYSTEM - Pakhomova, Ekaterina Gennadievna; Pavlovna, Natalia Grigorova; Vladislavovich, Monastyrev Pavel; Evgenievna, Natalia Semicheva (Journal of Applied Engineering Science, 2020)
Experimental studies of fine drip moisture and contaminants influence in the heat carrier on the heat transfer coefficient in the vortex heat exchanger of the heating system of gas control room were described. Pilot studies were carried out in two stages. At the first stage, the test values of coolant temperature decrease were analyzed due to heat removal for evaporation and heat transfer coefficient under idealized conditions without taking into account the effect of fine moisture and contaminants on the process of heat transfer to the blades in the vortex heat exchange apparatus. At the second stage, the heat transfer coefficient was studied under conditions close to actual operating conditions of vortex heat exchange element, when fine moisture and specific contaminants are in the natural gas which is in contact with water. As a result of the first stage of experimental studies, it was found that experimental values of heat carrier temperature decrease due to heat extraction for liquid evaporation on the surface of swirling swirler blade in vortex heat exchanger are slightly different from those determined theoretically. And they mainly decrease. Analysis of the heat transfer coefficient values under idealized conditions, obtained experimentally and calculated theoretically, shows their satisfactory convergence. This convergence is measurement error and data calculation. As a result of the second stage of pilot studies it was revealed that availability of disperse moisture increases heat transfer coefficient in 1,4%1,9 times. There is evaporation temperature increase as the concentration of contaminants bombarding the mirror of liquids increases. This fact also intensifies heat exchange process. Thus, as a result of experimental studies, the possibility of using a vortex heat exchange apparatus in a heating system of gas control station has been confirmed.